Impact of high intensity interval and moderate continuous training on plasma ratios of ProBNP1-108/BNP1-32 and NT-pro-BNP1-76/BNP1-32 after coronary artery bypass grafting surgery - Zare Karizak, Sara; Kashef, Majid; Gaeini, Abbas Ali; Nejatian, Mostafa (Frontiers in Physiology, 2023)
Background ProBNP1-108/ BNP1-32 and NT-pro-BNP1-76 / BNP1-32 ratios are significant indices for predicting complications after coronary artery bypass grafting (CABG) surgery. However, the effect of aerobic training types on these biomarkers has not been fully understood. So, the current study aimed to determine the impact of aerobic interval and continuous training programs on plasma ratios of ProBNP1-108/ BNP1-32 and NT-pro-BNP1-76 / BNP1-32 after CABG surgery. Method 36 patients were selected purposive (27 men and 9 women with mean of age 60.32±5.81 years, height 164.64 ± 9.25 cm, weight 73.86±14.23 kg, fat 32.30±4.28, SBP 142.67± 6.49, DBP 84.5±5.16 mmHg in a seated position at rest situation and functional capacity of 7.08±2.49 METs) and then divided randomly into three groups: control (C) group (without training program) moderate continuous training (MCT) and high-intensity interval training (HIIT) (exercise training program was performed 3 day/week for 8 weeks) with intensities 65% to 80% and 80% to 95% of reserve heart rate in order. Blood samples were taken 48 hours before the first session and 48 hours after the last training session to measure the plasma levels of ProBNP1-108, Corin enzyme, BNP1-32, and NT-pro-BNP1-76 using the enzyme-linked immunosorbent assay (ELISA) technique. Wilcoxon and kruskal wallis tests were used for analyzing data. Results The plasma corin enzyme was increased, and the ratios of proBNP1-108/ BNP1-32 and NT-pro-BNP1-76/BNP1-32 were reduced in both training groups compared with the control group (P=0.004, P=0000, P=0.016, P=0.003, P=0.009, P=0.016) when there was no significant difference was found between training groups (P=0.074, P=450, P=0.295). Conclusion Both HIIT and MCT in compared with inactivity have positive effects on ratios of ProBNP1-108/ BNP1-32, NT-pro-BNP1-76/BNP1-32 and could be effective to promote the health of coronary arteries and prevention of HF in post-CABG patients.